Strain echocardiography is related to fibrosis and ventricular arrhythmias in hypertrophic cardiomyopathy. (11th February 2016) - Haland, Trine F.; Almaas, Vibeke M.; Hasselberg, Nina E.; Saberniak, Jørg; Leren, Ida S.; Hopp, Einar; Edvardsen, Thor; Haugaa, Kristina H.
Abstract: Aims: Hypertrophic cardiomyopathy (HCM) patients are at risk of ventricular arrhythmias (VAs). We aimed to explore whether systolic function by strain echocardiography is related to VAs and to the extent of fibrosis by cardiac magnetic resonance imaging (CMR). Methods and results: We included 150 HCM patients and 50 healthy individuals. VAs were defined as non-sustained and sustained ventricular tachycardia and aborted cardiac arrest. Left ventricular function was assessed by ejection fraction (EF) and by global longitudinal strain (GLS) assessed by speckle tracking echocardiography. Mechanical dispersion was calculated as standard deviation (SD) of time from Q/R on ECG to peak longitudinal strain in 16 left ventricular segments. Late gadolinium enhancement (LGE) was assessed by CMR. HCM patients had similar EF (61 ± 5% vs. 61 ± 8%, P = 0.77), but worse GLS (−15.7 ± 3.6% vs. −21.1 ± 1.9%, P < 0.001) and more pronounced mechanical dispersion (64 ± 22 vs. 36 ± 13 ms, P < 0.001) compared with healthy individuals. VAs were documented in 37 (25%) HCM patients. Patients with VAs had worse GLS (−14.1 ± 3.6% vs. −16.3 ± 3.4%, P < 0.01), more pronounced mechanical dispersion (79 ± 27 vs. 59 ± 16 ms, P < 0.001), and higher %LGE (6.1 ± 7.8% vs. 0.5 ± 1.4%, P < 0.001) than patients without VAs. Mechanical dispersion correlated with %LGE ( R = 0.52, P < 0.001) and was independently associated with VAs (OR 1.6, 95% CI 1.1–2.3, P = 0.02) and improved risk stratification for VAs. Conclusion: GLS, mechanical dispersion, and LGE were markers of VAs in HCM patients. Mechanical dispersion was a strong independent predictor of VAs and related to the extent of fibrosis. Strain echocardiography may improve risk stratification of VAs in HCM.